Molecular Characterization of Mahabubnagar Goats using Microsatellite Markers - I. A. Shantha Latha; S. Sai Reddy; M. Gnana Prakash; Mahender, M. (International Journal of Livestock Research, 2019)
Mahabubnagar goats distributed in Mahabubnagar and in adjoining areas of Nalgonda and Rangareddy districts of Telangana, are well known for their production potential. The aim of the study is to estimate the genetic diversity and to asses genetic status of 40 unrelated Mahabubnagar goats using 15 microsatellite markers. A total of 123 alleles were amplified with an average of 10.00 ± 0.458 allels per locus and product size varied from 98 (OarFCB 20) to 287(INRABERN 185). The loci genotyped were found to be polymorphic with moderate to high informativeness. The high mean number of allels implies great allelic diversity which can be exploited for selection and indicate their suitability for diversity analysis. The overall mean expected and observed heterozygosity was 0.863 ± 0.011 and 0.778± 0.034. High heterozygosity values obtained may be due to intermixing of different populations probably during grazing period. The within breed diversity values revealed that there is wide genetic variability and the population was outbred in nature as indicated by negative inbreeding coefficient value in INRA023 and ETH10.All the 15 loci significantly deviated from Hardy Weinberg equilibrium.